1994
DOI: 10.1080/15428119491018727
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics and Construction: A Review of Potential Hazards in New Construction

Abstract: This article reviews potential ergonomic hazards in new construction work, summarizing findings from published literature and from a 15-month investigation of health hazards on a new construction site in suburban Washington, D.C. The review is structured to follow the sequence of events in the construction process. Ergonomic solutions are included where they have been developed. Highway work and renovation and demolition of existing structures, the segments of construction that are growing, are not discussed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(41 citation statements)
references
References 0 publications
3
36
0
2
Order By: Relevance
“…Guo et al [7,8] evaluated data from over 30 000 respondents and found that construction laborers and carpenters had the highest prevalence of back pain within the construction industry when comparing trades and industries. Among construction workers, back pain is endemic [5] in part due to workplace risk factors such as awkward postures, heavy lifting, pushing and pulling, and prolonged exertion [20,21,22,23,24,25,26,27].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Guo et al [7,8] evaluated data from over 30 000 respondents and found that construction laborers and carpenters had the highest prevalence of back pain within the construction industry when comparing trades and industries. Among construction workers, back pain is endemic [5] in part due to workplace risk factors such as awkward postures, heavy lifting, pushing and pulling, and prolonged exertion [20,21,22,23,24,25,26,27].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Existe evidencia que los desórdenes músculo esqueléticos son los principales problemas en la industria de la construcción [4], debido a que las actividades que se realizan en este tipo de industria comúnmente requieren elevada demanda físi-ca de trabajo, posturas forzadas, levantamiento de cargas, uso frecuente de herramientas manuales y otros esfuerzos enérgicos [5]. Se ha demostrado que los trabajadores de la construcción muestran elevado riesgo de desarrollar lesiones músculo esqueléticas relacionadas con el trabajo en espalda baja, hombros, manos, muñecas y rodillas, lo cual genera elevados costos para las empresas y la fuerza de trabajo [5][6][7].…”
Section: Problemaunclassified
“…Se ha demostrado que los trabajadores de la construcción muestran elevado riesgo de desarrollar lesiones músculo esqueléticas relacionadas con el trabajo en espalda baja, hombros, manos, muñecas y rodillas, lo cual genera elevados costos para las empresas y la fuerza de trabajo [5][6][7].…”
Section: Problemaunclassified
“…Working in the construction industry has been considered to have ergonomic problem due to the fact that it requires working above the shoulder and below the knee height (Schneider & Susi, 1994). Similarly, Samuelsson and Lundholm (2006) observed that the ergonomic problem in the construction industry could be as a result of heavy lifting, working on one side, and strenuous work postures.…”
Section: Introductionmentioning
confidence: 99%